The Influence of Problem Based Learning Model on Students' Interest in Learning and Creative Thinking Skills in Mathematics Subjects in Elementary Schools - Marisda Sipahutar; Citra Ayu; Samsurijal (Institute of Educational, Research, and Community Service, 2024)
This study aims to investigate the effect of the Problem Based Learning (PBL) learning model on students' learning interest and creative thinking skills in mathematics subjects in elementary schools. The research design used was a quasi-experiment with two groups: class IIIA as the control group (n = 20) and class IIIB as the experimental group (n = 19). Data collection was carried out during the period from May 13 to June 7, 2024 through questionnaires and tests. Data analysis involved normality tests, homogeneity tests, and Mann-Whitney tests to test differences between the two groups. The results of the analysis showed that the implementation of PBL significantly increased students' learning interest (p = 0.000) and creative thinking skills (p = 0.000) compared to conventional learning methods. These findings indicate that the PBL model is an effective strategy to improve the quality of mathematics learning in elementary schools. The implications of this study are that PBL can be used as a basis for curriculum development and teacher training, which aims to design more interactive, relevant, and contextual learning for students.